Role of Astrocytic Inwardly Rectifying Potassium (Kir) 4.1 Channels in Epileptogenesis - Kinboshi, Masato; Ikeda, Akio; Ohno, Yukihiro (Frontiers in Neurology, 2020)
Astrocytes regulate potassium and glutamate homeostasis via inwardly rectifying potassium (Kir) 4.1 channels in synapses, maintaining normal neural excitability. Numerous studies have shown that dysfunction of astrocytic Kir4.1 channels is involved in epileptogenesis in humans and animal models of epilepsy. Specifically, Kir4.1 channel inhibition by KCNJ10 gene mutation or expressional down-regulation increases the extracellular levels of potassium ions and glutamate in synapses and causes hyperexcitation of neurons. Moreover, recent investigations demonstrated that inhibition of Kir4.1 channels facilitates the expression of brain-derived neurotrophic factor (BDNF), an important modulator of epileptogenesis, in astrocytes. In this review, we summarize the current understanding on the role of astrocytic Kir4.1 channels in epileptogenesis, with a focus on functional and expressional changes in Kir4.1 channels and their regulation of BDNF secretion. We also discuss the potential of Kir4.1 channels as a therapeutic target for the prevention of epilepsy.